1991
DOI: 10.1038/bjc.1991.300
|View full text |Cite
|
Sign up to set email alerts
|

Argyrophilic nucleolar organiser region counts and prognosis in pharyngeal carcinoma

Abstract: Summary The prognostic significance of argyrophilic nucleolar organiser regions (AgNORs)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1994
1994
2008
2008

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…For AgNOR staining and counting 3 gm thick sections taken to an aqueous medium were stained with the AgNOR method of Ploton et al (1986), as previously described (Pich et al 1991). Random fields, excluding areas of necrosis, were independently examined by two pathologists (AP and LC) using a 100 x oil immersion lens; at least 100 tumour cells were counted in each case.…”
Section: Methodsmentioning
confidence: 99%
“…For AgNOR staining and counting 3 gm thick sections taken to an aqueous medium were stained with the AgNOR method of Ploton et al (1986), as previously described (Pich et al 1991). Random fields, excluding areas of necrosis, were independently examined by two pathologists (AP and LC) using a 100 x oil immersion lens; at least 100 tumour cells were counted in each case.…”
Section: Methodsmentioning
confidence: 99%
“…AgNOR staining was performed according to Ploton et al [37] as previously described [33]. AgNORs were counted according to Crocker et al [9], and the mean number per nucleus was calculated in each case.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies concerning the prognostic significance of AgNOR counts in squamous cell carcinomas of the head and neck are in accordance with our findings and show that high values for mean AgNOR counts concur with poor prognosis. [16][17][18][19][20] Two of these studies 17,19 applied multivariate analysis and both showed that mean AgNOR counts was the strongest single parameter in separating prognostically favorable and unfavorable cases. Contrary to Pich et al 17 and Bochmü hl et al 19 studying pharyngeal and laryngeal carcinomas, we found that T1-T2 carcinomas had significantly lower mean AgNOR counts than did T3-T4 tumors.…”
Section: Discussionmentioning
confidence: 99%
“…The N classification did not influence the mean AgNOR counts. 17,19 The mean number of AgNORs per tumor nucleus is the method employed by most investigators. Previous studies on head and neck squamous cell carcinomas revealed an overall mean AgNOR count ranging from 4.3 to 10.7.…”
Section: Discussionmentioning
confidence: 99%